College Students' Test Anxiety and Listening Test Scores: CB and MAC-Based Psychoeducation Vs. No Treatment Control. Issue 2 (3rd April 2022) - Huffman, Jonathan Michael; Provorse, Dave; Hockett, Jericho; Kerr, Barbara A.
ABSTRACT: The purpose of this study was to compare two psychoeducation interventions of cognitive behavioral (CB) and mindfulness acceptance commitment (MAC)-based models against a no treatment control (NTC) group with test anxiety and exam scores on a written and music listening test. Three sections of an undergraduate course participated ( N = 104), with each assigned to a condition: (a) CB psychoeducation ( n = 40), (b) MAC psychoeducation ( n = 26), and (c) NTC group ( n = 38). Participants in the CB and MAC psychoeducation received two 20-minute PowerPoint lectures that described the theoretical principles of their assigned condition and were encouraged to utilize the material in managing their test anxiety. CB and MAC-based psychoeducation improved participants' knowledge of these models and improved test scores on music listening tests. Results suggest that CB and MAC-based psychoeducation are promising interventions for improving listening test scores and should be further studied.